Articular Cartilage Fragmentation Improves Chondrocyte Migration by Upregulating Membrane Type 1 Matrix Metalloprotease. (December 2021) - Lei, Yunliang; Peng, Jiabin; Dai, Zhu; Liao, Ying; Liu, Quanhui; Li, Jian; Jiang, Yonghui
Objective: This study was undertaken to elucidate the mechanism of improved chondrocyte migration after juvenile articular cartilage fragmentation. Design: In vitro organ culture with rabbit cartilage fragments and cell culture with rabbit chondrocytes were performed. In part A, minced juvenile cartilage fragments (~0.5 × 0.5 × 0.5 mm) from rabbits, planted in gelatin sponge and fibrin glue, were cultured for 2, 4, or 6 weeks in vitro and compared with the cartilage chunks (~4 × 4 × 1 mm) and membrane type 1 matrix metalloprotease (MT1-MMP) inhibitor groups. Chondrocyte outgrowth was evaluated on histology and confocal laser scanning microscopy. MT1-MMP expression was compared between the cartilage fragment group and the cartilage chunks group. In part B, articular chondrocytes were harvested from juvenile rabbits, MT1-MMP was transfected into the cells, and cell migration was evaluated using the Transwell and wound healing tests. Results: The histology and confocal microscopy results revealed that cell accumulation occurred at the edge of cartilage fragments, and outgrowth was better in the cartilage fragment group than those in the cartilage chunks group. Similar results were observed for MT1-MMP expression. After MT1-MMP inhibition, cells did not accumulate at the edge of the cartilage fragments, and chondrocyte outgrowth did not occur. Furthermore, overexpression of MT1-MMP enhanced the migration of articular chondrocytes. Conclusions: Juvenile articular cartilage fragmentation improved chondrocyte migration by upregulating MT1-MMP.